2023
DOI: 10.1029/2023gl105066
|View full text |Cite
|
Sign up to set email alerts
|

The Lasting Legacy of Megaflood Boulder Deposition in Mountain Rivers

S. M. Morey,
C. M. Shobe,
K. W. Huntington
et al.

Abstract: Infrequent, large‐magnitude discharge (>106 m3/s) outburst floods—megafloods—can play a major role in landscape evolution. Prehistoric glacial lake outburst megafloods transported and deposited large boulders (≥4 m), yet few studies consider their potential lasting impact on river processes and form. We use a numerical model, constrained by observed boulder size distributions, to investigate the fluvial response to boulder deposition by megaflooding in the Yarlung‐Siang River, eastern Himalaya. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Thaler and Covington (2016) found that channel steepness in their study area was correlated with boulder size and percent boulder coverage rather than underlying bedrock lithology. Some field studies have also sought to quantify the influence of immobile cover from boulders using UAV surveys and satellite imagery (Carr et al, 2023;Morey et al, 2024;Shobe et al, 2020). They map the presence of large, immobile boulders in the channel and then apply different quantitative metrics, such as boulder concentration (Shobe et al, 2020) or the percentage of the channel area covered by these boulders (Carr et al, 2023).…”
Section: Quantifying Sediment Cover Effects In the Fieldmentioning
confidence: 99%
“…Thaler and Covington (2016) found that channel steepness in their study area was correlated with boulder size and percent boulder coverage rather than underlying bedrock lithology. Some field studies have also sought to quantify the influence of immobile cover from boulders using UAV surveys and satellite imagery (Carr et al, 2023;Morey et al, 2024;Shobe et al, 2020). They map the presence of large, immobile boulders in the channel and then apply different quantitative metrics, such as boulder concentration (Shobe et al, 2020) or the percentage of the channel area covered by these boulders (Carr et al, 2023).…”
Section: Quantifying Sediment Cover Effects In the Fieldmentioning
confidence: 99%